Smoking and looked-after children: a mixed-methods study of policy, practice, and perceptions relating to tobacco use in residential units - Huddlestone, Lisa; Pritchard, Catherine; Ratschen, Elena (MDPI, 2016)
Despite the implementation of smoke-free policies by local authorities and a statutory requirement to promote the health and well-being of looked-after children and young people in England, rates of tobacco use by this population are substantially higher than in the general youth population. A mixed-methods study, comprising a survey of residential care officers in 15 local authority-operated residential units and semi-structured, face-to-face interviews with residential carers in three local authority-operated residential units, was conducted in the East Midlands. Survey data were descriptively analysed; and interview data were transcribed and analysed using thematic framework analysis. Forty-two care officers (18% response rate) completed the survey, and 14 participated in the interviews. Despite reporting substantial awareness of smoke-free policies, a lack of adherence and enforcement became apparent, and levels of reported training in relation to smoking and smoking cessation were low (21%). Potential problems relating to wider tobacco-related harms, such as exploitative relationships; a reliance on tacit knowledge; and pessimistic attitudes towards LAC quitting smoking, were indicated. The findings highlight the need for the development of comprehensive strategies to promote adherence to and enforcement of local smoke-free policy within residential units for looked-after children and young people, and to ensure appropriate support pathways are in place for this population.